Hydroxyapatite Nanoparticles Facilitate Osteoblast Differentiation and Bone Formation Within Sagittal Suture During Expansion in Rats [Corrigendum] - Liang W; Ding P; Li G; Lu E; Zhao Z (Dove Medical Press, 2021)
Liang W, Ding P, Li G, Lu E, Zhao Z. Drug Des Devel Ther. 2021;15:905– 917. The authors have advised Figure 3 on page 911 is incorrect. Due to an error at the time of figure assembly part of the 25 μg/ml and 100 μg/ml groups in figure part D were duplicated. The correct Figure 3 is shown in Download Article. The authors apologize for this error and advise it does not affect the results of the paper. Read the original articlePrevious corrigendum has been published